The Influence of Artificial Intelligence on Customer Experience (Study of Maxim Users in Surabaya, East Java) - Terenggana, Candra Astra (Economics Studies and Banking Journal (DEMAND), 2024)
This study aims to investigate the impact of artificial Intelligence (AI) on customer experience (CX) for customers of the Maxim transportation application in Surabaya. With the aid of focusing on the implementation of the AI era in personalizing services, growing operational performance, and responding quickly to customer needs, this research explores the fantastic impact on the customer. The research method makes use of a deductive approach, accumulating records from Maxim customers in Surabaya through surveys, interviews, and information analysis. The research results display that AI permits deeper personalization and designs more adaptive user experiences. The study's conclusion highlights that the integration of AI in Maxim's transportation offerings extensively increases customer experience and opens up commercial enterprise opportunities. But, demanding situations related to ethics and facts protection need to be cautiously taken into consideration. This study affords a holistic view of the way artificial intelligence may be a tremendous driver in creating better customer studies in the context of transportation offerings in Surabaya.